1985
DOI: 10.1042/bj2280161
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a multicatalytic high-molecular-mass proteinase from rat skeletal muscle

Abstract: A proteolytic enzyme was purified from the post-myofibrillar fraction of rat skeletal muscle. The purification procedure consisted of fractionation of the muscle extract by (NH4)2SO4, chromatography on DEAE-Sephacel, fast protein liquid chromatography on Mono Q and gel filtration on Sepharose 6B. The enzyme preparation appeared to be homogeneous as judged by disc electrophoresis in polyacrylamide gels and by immunoelectrophoresis. The isoelectric point of the proteinase is at 5.1-5.2. The enzyme has an Mr of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
84
2
3

Year Published

1988
1988
2002
2002

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(95 citation statements)
references
References 19 publications
6
84
2
3
Order By: Relevance
“…A neutral proteinase has been identified in a variety of eukaryotic cells and has been designated 'multicatalytic proteinase' (MCP) since it appears to contain more than one active site for catalysis of peptide-bond cleavage [1][2][3]. The latent enzyme which can be activated by SDS and fatty acids [1,4,5], by phospholipids [6] as well as by polylysine [3] is localized in the cytoplasm [3], in the cell nucleus [7] or in both compartments [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A neutral proteinase has been identified in a variety of eukaryotic cells and has been designated 'multicatalytic proteinase' (MCP) since it appears to contain more than one active site for catalysis of peptide-bond cleavage [1][2][3]. The latent enzyme which can be activated by SDS and fatty acids [1,4,5], by phospholipids [6] as well as by polylysine [3] is localized in the cytoplasm [3], in the cell nucleus [7] or in both compartments [8].…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme purified from rat skeletal muscle has a molecular mass of 650 kDa [2]. A 19 S ribonucleoprotein (RNP) with a similar subunit pattern has been identified in a number of eukaryotic cells as reviewed in [9].…”
Section: Introductionmentioning
confidence: 99%
“…la, only one band was detected in the non-denatured gel. And SDS gel elctrophoresis of the purified protease demonstrated its multisubunit structure, which was the same as that of the multicatalytic proteinase, ingensin, from other sources [2][3][4][5]11] (fig.lb). These results indicated that the enzyme sample was highly purified, i.e.…”
Section: Confirmation Of the Purity Of The Multicatalytic Proteinasementioning
confidence: 91%
“…The multicatalytic proteinase, ingensin, is a cytosolic protease which has an unusually high molecular mass, 650-750 kDa, and is composed of multiple subunits of 25-35 kDa [1][2][3][4][5]. One of the important characteristics of the enzyme is the multiplicity of its activity.…”
Section: Introductionmentioning
confidence: 99%
“…This particle with a sedimentation coefficient of approximately 20 S (molecular mass about 750 kDa) is composed of a characteristic set of at least 13 non-identical polypeptide subunits with molecular masses between 20 and 35 kDa [2][3][4]. The individual subunits may each have a unique catalytic property, i.e.…”
Section: Introductionmentioning
confidence: 99%